Economic Policies and FDI Inflows to Emerging Market Economies - Arbatli Saxegaard, Elif (IMF Working Papers; Working Paper, 2011)
This paper investigates the determinants of FDI inflows to emerging market economies, concentrating on the effects of economic policies. The empirical analysis also addresses the role of external push factors and of political stability using a domestic conflict events database. The results suggest that lowering corporate tax rates and trade tariffs, adopting fixed or managed exchange rate policies and eliminating FDI related capital controls have played an important role. Domestic conflict events and political instability are found to have significant negative effects on FDI, which highlights the role of incluside policies to promote growth and avoid sudden stops of FDI inflows.